Responsive Façades: Parametric Control of Moveable Tilings - Datta, Sambit; Hobbs, M. (University Putra Malaysia Press, 2013)
The challenge of developing adaptive, responsive low-energy architecture requires new knowledge about the complex and dynamic interaction between envelope architecture, optimization between competing environmental performance metrics (light, heat and wind indices) and local climate variables. Advances in modeling the geometry of building envelopes and control technologies for adaptive buildings now permit the sophisticated evaluation of alternative envelope configurations for a set of performance criteria. This paper reports on a study of the parametric control of a building envelope based on moveable façade components, acting as a shading device to reduce thermal gain within the building. This is investigated using two alternative tiling strategies, a hexagonal tiling and a pentagonal tiling, considering the component design, support structure and control methods.